Analysis and design of low-distortion CMOS source followers - Fan, Xianping (2009)
This paper presents the analysis of CMOS technology based nMOS source follower (NSF), pMOS source follower (PSF), and cascade-complementary source follower(CCSF) using a simplified large-signal model. Three new large-signal second harmonic equations and high-frequency transfer functions are derived. Optimization strategies which permit optimal design for low-distortion NSF, PSF, and CCSF are proposed. This includes a new complementary linearization method introduced for CCSF. With employment of dedicated optimization, the CCSF can achieve significantly better low-distortion broad-band characteristics than the other schemes. Comparative HSPICE simulated results for the three source followers have shown good agreement with the second-order analytical results using the simplified BSIM3 model